Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat Kemiskinan dan Pengangguran Terhadap Indeks Pembangunan Manusia pada 6 Kabupaten/Kota di Provinsi Kalimantan Selatan Tahun 2010-2022 - Rohmawati, Siti; Anshar Nur, Muhammad (PPJP ULM, 2025)
The This study aims to analyze the effect of economic growth, poverty level and unemployment simultaneously and partially and which factor has the most dominant effect on the Human Development Index in 6 districts / cities in South Kalimantan Province in 2010-2022. This type of research is quantitative with secondary data and the data analysis technique used is panel data regression analysis with data calculations using E-views 12 software. This study found that in 6 districts / cities in South Kalimantan Province in 2010-2022, economic growth, poverty levels and unemployment simultaneously had a significant effect on the Human Development Index. Partially, economic growth and poverty levels have a significant effect, while unemployment has an insignificant effect and the poverty rate is the most dominant factor affecting the Human Development Index in 6 districts / cities in South Kalimantan Province in 2010-2022.